Contribution plots: A missing link in multivariate quality control - Miller, Paige; Swanson, Ronald E.; Heckler, Charles E. (Zielona Góra: Uniwersytet Zielonogórski)
Most multivariate quality control techniques involve plotting and analysis of a set of surrogate variables, such as T2, scores and residuals. The number of these surrogate variables can be considerably smaller than the number of original variables. However, it is often difficult to determine the source of a problem when the process is identified as being out of control by one of the surrogate variables.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka